A COMPARATIVE ANALYSIS OF METHODS FOR CREATING AN IRONIC MEANING IN UZBEK AND ENGLISH LANGUAGES. - Abduqodirova Madina Abduqayum qizi (TADQIQOTLAR, 2025)
Annotation. This article offers a comparative study of how irony is expressed in the Uzbek and English languages. It investigates the linguistic methods both languages use to create irony, including elements like tone, wordplay, and contextual clues. The paper explores different types of irony—such as verbal, situational, and dramatic—and looks at how these are shaped by cultural and contextual factors in each language. By comparing the use of irony in daily communication and literature, the article highlights both the similarities and differences in ironic expression between Uzbek and English. The research provides valuable insights into how language structure and cultural influences affect the way irony is formed and understood in these two languages.